Emerging Skill Needs in Health Care and the Future of Nursing - Dunkel, Torsten [Verfasser] (My University, 2016)
"As European society greys, healthcare and related social services are becoming increasingly important. The demand for those services that are provided by the public sector in many EU countries is creating unprecedented pressures on health care systems. To mitigate these pressures, the sector needs personnel with the right skills and competence. New care needs, the expansion of health information technology and telemedicine will impact on the nature of skills demand in the sector: rising requirements of e-skills, clinical knowledge and the creation of new roles for medium and lower qualified professionals, for example in geriatric care and eHealth workers in clinical, social care, informatics and administration. Besides, health professionals increasingly need broader soft skills such as communication, team building to work interprofessionally in multidisciplinary teams. This contribution sums up future challenges for the healthcare sector in Europe with a focus on new skills required by nurses. In the context of recent EU policy initiatives technology enhanced learning and interprofessional collaboration in nursing education are suggested to mediate task shifts, changing roles and new skill-mixes to respond to growing practice requirements in the field." (author's abstract; BIBB-Doku)
Keywords: G 2.3.4 Qualifikationswandel; G 1.2.3.2 Anforderungen & Bedarfe; S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); I 2.2 Europa; Gesundheitswesen; Fachkräftebedarf; Qualifikationsanforderung; Pflegeberuf; Care work; Qualifikationsentwicklung; Europa